2018
DOI: 10.1007/5584_2018_233
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Regarding Influenza and Influenza Vaccination in General Population: Results of a National Survey in Poland

Abstract: For the past 10 years, influenza vaccination coverage rate in Poland remains at a low 3% threshold. This low rate may be related to the unsatisfactory knowledge of vaccination, influenza, and misperception of health risks in the general population. To examine these issues, we used an online questionnaire consisting of 12 closed questions. The basic knowledge on influenza and vaccination was examined. The questionnaire was completed by 1669 persons, mostly young women. Generally, 73% of respondents passed the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The previously mentioned large-scale EU investigation of vaccine confidence highlighted that between 2015 and 2018, Poland noted the largest decrease in public confidence in the importance, effectiveness and safety of vaccines. Previous more detailed investigations [12][13][14][15][16] revealed that Polish residents have a positive overall perception of vaccinations, but poor knowledge of vaccines and vaccine-preventable diseases and concerns about vaccine safety. These investigations also highlighted a major role of physicians as the most used and the most trusted source of information on vaccination for parents.…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned large-scale EU investigation of vaccine confidence highlighted that between 2015 and 2018, Poland noted the largest decrease in public confidence in the importance, effectiveness and safety of vaccines. Previous more detailed investigations [12][13][14][15][16] revealed that Polish residents have a positive overall perception of vaccinations, but poor knowledge of vaccines and vaccine-preventable diseases and concerns about vaccine safety. These investigations also highlighted a major role of physicians as the most used and the most trusted source of information on vaccination for parents.…”
Section: Introductionmentioning
confidence: 99%
“…A similar percentage of participants declared their willingness to get vaccinated against influenza during pregnancy in the upcoming influenza season; however, almost 70% of participants were strongly opposed to the vaccination. For many years, IVC in Poland has been very low and remained below 4% [7,8]. IVC among the survey participants was comparable to the general population and much lower than that reported in other countries.…”
Section: Discussionmentioning
confidence: 73%
“…In patients with chronic diseases, as well as the elderly, immunization coverage is higher than in the general population; however, this still remains well below the recommended level, which is the 75% uptake in key risk groups [13,25,26]. The attitude toward influenza infection and vaccination is different in Poland; it is not regarded as an important vaccination and there is a lack of awareness of its need -in a national survey in Poland [24,25] important gaps in the knowledge on influenza vaccination were found in the general Polish population.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccination is not a mandatory vaccination in Poland, and costs fall on the patient. Overall, it is not a popular vaccine and uptake is very low with the influenza vaccination uptake rate remaining at a 3% threshold nationally in the past 10 years [24]. The influenza vaccination uptake rate differs widely in Poland and depends much on the age and risk group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation